HOW'S STUDENT CHARACTER IN DIGITAL ERA? A COMPREHENSIVE STUDY OF PAI TEACHERS ROLE IN SHAPING STUDENTS' RELIGIOUS CHARACTER - Munawaroh Munawaroh; Akhmad Khoiri (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
In the digital era, technological developments affect almost all aspects of life, including education. Technology brings easy access to information but also has the potential to give rise to value deviations in the younger generation. Islamic Religious Education (PAI) teachers have a big responsibility in shaping students' religious character so that it remains in line with Islamic values even though they are faced with changing times. Purpose this study focuses on exploring and analyzing data related to the Role of PAI Teachers in Forming Students' Religious Character in the Digital Era at SMPIT Daarul Ilmi.The research method is descriptive qualitative. The results of the research show that PAI teachers at SMPIT Daarul Ilmi use various creative, technology-based approaches to integrate religious values into students' lives, while managing the challenges that arise. Through the use of technology and learning based on religious values that are relevant to digital life, PAI teachers at SMPIT Daarul Ilmi can help students develop characters who are not only intellectually intelligent but also morally and religiously. Namely honesty, responsibility, discipline, empathy and social concern, respect and tolerance.